Sustainability science for social, economic, and environmental development - Ghosh, Nilanjan; Goswami, Anandajit, 1980-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2014)
"This book investigates the role of sustainability in the everyday lives of ordinary citizens, including issues of economy, social interaction, exploitation of natural resources, and sources of renewable energy"--Provided by publisher.
Economic growth, sustainable development, and the role of markets -- On value and price of environmental resources -- Altruism, social networks, and social capital: some interlinkages -- Justice, migration, agriculture, and sustainability -- Feminism and tenets of philosophy of economics: the sustainability connections -- Labour observatories for agricultural policymaking and sustainable development -- Biofuels and renewables: implications for people, planet, policies, politics -- Biofuel sustainability and transition pathways -- Valuation and market-based pricing of economic and ecosystem services of water resources -- "Virtual water" and Occam's razor: an explanation from the perspective of economics of water -- Water scarcity and conflicts: can water futures exchange in South Asia provide the answer? -- Two first generation biofuel (biodiesel, bioethanol) and sustainability: some other realities for India and trade patterns -- Connections between spectrum allocation, social capital and sustainability -- Story of live discussion in autos of Delhi: what do they say about sustainability? -- Energy and emission linkages from the three wheeler autorickshaws of Kolkata: an exploratory analysis of the impact on economic, environmental, social dimensions of sustainability -- Economics, environmental policy, trade and sustainability -- Can a poor be vegetarian for addressing sustainability?
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 02/28/2014).
Keywords: Sustainable development; Economic development; Economic growth; Energy security; Environmental management; Gender issues; International trade; Natural resource economics; Renewable resources; Social networks and social capital; Electronic books